Steel Plate Analysis by Finite Elements - Firkins, Norman L. (Engineering Journal, 1969)
The finite element method is becoming a popular as well as practical way of analyzing plates, shells, and related structures. The technique of modeling an elastic structure into an assemblage of discrete bars or sections and interconnecting these elements by a finite number of joints or nodal points is not new. The growth and development of the finite element method has been greatly enhanced by the high speed digital computer and matrix methods in structural mechanics. Extended finite element formulation is being carried on to increase the potential of this method in the areas of plasticity, vibration, and three-dimensional stress applications. Although continuous investigation is being undertaken, it might be in order to review the basic finite element formulation and provide a simplified method of evaluation for the practicing engineer.